Severity of child pedestrian injuries due to bonnet‐type‐vehicle collision. Issue 5 (30th July 2013) - Hitosugi, Masahito; Kawato, Hitoshi; Gomei, Sayaka; Mizuno, Koji; Tokudome, Shogo
Abstract Background The aim of this study was to clarify the pattern of child pedestrian injury, injury severity, and its relation to collision velocity in bonnet‐type‐vehicle collision. Methods In‐depth data were retrospectively collected from the Institute for Traffic Accident Research and Data Analysis on pedestrians younger than 13 years old with any bodily injuries from collisions with bonnet‐type vehicles between 1993 and 2004. Results Forty‐seven patients from 43 collisions with a mean age of 6.9 ± 2.5 years were included in the study. Injury severity was not significantly different between patients who were hit by the front of the vehicle and those who were hit by the side of the vehicle. In front collisions, impact with the vehicle was associated with significantly higher Abbreviated Injury Scale (AIS) scores than those for impact with the road, especially for the lower extremities (mean: 1.2 vs 0.2, P < 0.001). Injury severity of the lower extremities and collision velocity were examined. The estimated collision velocity of the vehicle was not significantly different between patients with lower extremity AIS scores of 0 or 1 and those of 2 or 3. Conclusions Some pediatric pedestrians suffer from collisions with bonnet‐type vehicles without lower extremity fractures owing to the characteristics of child pedestrians. Providing injury prevention programs for children in communities and schools, developing active safety devices in the vehicle, and modifying the vehicle body to a pediatric pedestrian‐friendly structure may increase pedestrian protection.